THREE-DIMENSIONAL NUMERICAL HYDRODYNAMIC SIMULATION OF ON- AND OFF-STATES IN MICROQUASARS AND QUASARS - Nazarenko, V. V.; Nazarenko, S. V. (Одеські астрономічні публікації, 2014)
As is shown in the present computations performed using three-dimensional numerical astrophysical methods, in microquasars in the course of precession of the accretion disc blown by the donor’s wind the on- and off-states start being generated in the disc. In our case, the transition between these states takes 30-40 minutes of the orbital time. In the off-state the temperature changes discretely, i.e. such a change appears as separate sharp peaks, which almost merge with each other over time.